Educational Robotics With On-Device AI: An Interactive System Based on the Phi-3 Mini Small Language Model Running on Conventional Hardware - Souza, Vitor Amadeu (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This work presents an educational robotics system integrating speech recognition, a Small Language Model (SLM), and speech synthesis on GPU-free hardware. It uses Google Speech Recognition, Phi-3 Mini via Ollama with 4-bit quantization, pyttsx3, and Pygame. Experiments on an Intel Core i5-3570 with 16 GB RAM evaluated five interactions. The average latency was 30.16 s, with speech recognition (6.80 s), SLM processing (8.06 s), and synthesis (15.30 s). Speech synthesis was the main bottleneck (50.73%), followed by SLM (26.72%) and recognition (22.55%). Results demonstrate feasibility on low-cost hardware while highlighting the need for latency optimization for more natural interaction.